2007
DOI: 10.1196/annals.1379.011
|View full text |Cite
|
Sign up to set email alerts
|

Linking Brain Imaging and Genomics in the Study of Alzheimer's Disease and Aging

Abstract: My colleagues and I have been using positron emission tomography (PET) and magnetic resonance imaging (MRI) to detect and track the brain changes associated with Alzheimer's disease (AD) and normal brain aging in cognitively normal persons with two copies, one copy, and no copies of the apolipoprotein E (APOE) epsilon4 allele, a common AD susceptibility gene. In this review article, I consider how brain imaging techniques could be used to evaluate putative AD prevention therapies in cognitively normal APOE eps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…These data indicate that reproductive senescence might accelerate the decline in mitochondrial bioenergetics, linking reproductive senescence to the development of a hypometabolic brain phenotype clinically observed in prodromal AD brains [36]. Further, multiple bioenergetic metabolic phenotypes evident at the onset of reproductive senescence indicates the activation of a combination of adaptive responses.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that reproductive senescence might accelerate the decline in mitochondrial bioenergetics, linking reproductive senescence to the development of a hypometabolic brain phenotype clinically observed in prodromal AD brains [36]. Further, multiple bioenergetic metabolic phenotypes evident at the onset of reproductive senescence indicates the activation of a combination of adaptive responses.…”
Section: Discussionmentioning
confidence: 99%
“…Functional brain imaging with fluorodeoxy-glucose ( 18 F), a radiotracer used to study glucose utilization as a surrogate measure of mitochondrial activity, revealed that the cerebral metabolic rate was reduced in both AD patients and in cognitively normal apoE4 carriers in their 20s and 30s, several decades before the typical onset of dementia (Reiman, 2007; Reiman et al, 2004). Gene-expression profiles in postmortem human brain tissue showed a significant association between apoE genotype and the expression levels of multiple mitochondrial respiratory enzymes (Conejero-Goldberg et al, 2011), specifically, a reduction in the expression of electron transport–chain genes in apoE4 carriers (Liang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although the causes of late-onset AD pathology are unknown, family studies have demonstrated that complex genetic and environmental mechanisms contribute to disease risk [1,2]. Since the elucidation of the APOE locus in 1993 [3], over 660 candidate genes for AD risk have been identified, however results are inconsistent between studies [4].…”
Section: Introductionmentioning
confidence: 99%